Kajian Penerapan Sistem Manajemen Terintegrasi Terhadap Kinerja Karyawan - Anggi Setiawan; I Wayan Widia; Ida Bagus Putu Gunadnya (Jurnal BETA (Biosistem dan Teknik Pertanian), 2019)
The aims of this research were to measure the employees level of understanding on Integrated Management System (IMS) implementation, to analyze employees performances, and to determine the effect of IMS implementation on employees performances in canned pineapple company. Measured IMS implementation (X) aspect include customer (X 1), food safety and halal (X 2), safety and health (X 3), environmental (X 4), and law (X5). Meanwhile, measure demployees performances (Y) include clear thinking (Y1), collaboration (Y2), creative and courage (Y3), expertise (Y4), and external focus (Y5). This research used survey methodology involving 346 respondents who selected by using stratified random sampling methodology. Each of variables was determined by five indicators with five level measurement scale. The result showed that the avarage level of employee understanding on IMS implementation was 4,33 which means understand and the average employees performances was 4,18 which means good. The IMS implementation has positive and signifiant effect on employees performances. The effect of IMS implementation on employees clear thinking was showed by multiple linear regression Y1= 0,364X1+ 0,264X2+ 0,146X3+ 0,205X5(R2= 0,992), on employee collaboration is showed by equation Y2= 0,302X1+ 0,187X2+ 0,264X3+ 0,233X4(R2= 0,993),on employee creative and courage is showed by equation Y3= 0,268X1+0,299X2+ 0,209X3+0,215X4(R2= 0,992), on employee expertise is showed by equation Y4= 0,315X1+ 0,418X2+0,191X3(R2= 0,990), and on employee external focus is showed by equation Y5= 0,379X1+0,375X2+ 0,194X3(R2= 0,989).